Revised guidelines for the clinical management of Lynch syndrome (HNPCC): recommendations by a group of European experts. Issue 6 (13th February 2013) - Vasen, Hans F A; Blanco, Ignacio; Aktan-Collan, Katja; Gopie, Jessica P; Alonso, Angel; Aretz, Stefan; Bernstein, Inge; Bertario, Lucio; Burn, John; Capella, Gabriel; Colas, Chrystelle; Engel, Christoph; et al.
Abstract : Lynch syndrome (LS) is characterised by the development of colorectal cancer, endometrial cancer and various other cancers, and is caused by a mutation in one of the mismatch repair genes: MLH1, MSH2, MSH6 or PMS2 . In 2007, a group of European experts (the Mallorca group) published guidelines for the clinical management of LS. Since then substantial new information has become available necessitating an update of the guidelines. In 2011 and 2012 workshops were organised in Palma de Mallorca. A total of 35 specialists from 13 countries participated in the meetings. The first step was to formulate important clinical questions. Then a systematic literature search was performed using the Pubmed database and manual searches of relevant articles. During the workshops the outcome of the literature search was discussed in detail. The guidelines described in this paper may be helpful for the appropriate management of families with LS. Prospective controlled studies should be undertaken to improve further the care of these families.